Analisis Kesalahan Siswa dalam Mengerjakan Soal Matematika Materi Aritmatika Sosial dengan Gaya Kognitif Field Dependent dan Field Independent Di Kelas VII SMP Negeri 4 Kuala Tungkal - Marbun, Novriandi Alpiansyah; Fitriani, Silvia; Zulyadaini, Zulyadaini (PHI: Jurnal Pendidikan Matematika, 2022)
The purpose of this study was to analyze the errors made and to describe the causes of errors in students with field-dependent and field-independent cognitive styles in solving social arithmetic problems based on Newman's error analysis method. The subjects of this study were 3 subjects taken from class VII SMP Negeri 4 Kuala Tungkal, where 1 student had a field-independent cognitive style and 2 students had a field-dependent cognitive style. The instruments in this study were GEFT test question sheets, social arithmetic question sheets, and interview guidelines. The results of the study showed that there were errors made by subjects with field-independent cognitive style based on Newman's error analysis. Transformation error, where the subject does not write the approach model or mathematical arithmetic operation model on the given task sheet. Process skill errors and conclusions writing errors. The 2 subjects with field-dependent cognitive style also met several indicators of Newman's error in solving social arithmetic problems. Misunderstood the problem, transformation error, skill error and conclusion writing error. The causes of errors made by subjects with field-independent and field-dependent cognitive styles are almost the same, namely being less thorough, not knowing the steps used to solve problems, rushing in solving problems, and students' habits in solving story problems, for example students not writing conclusions.